2022
DOI: 10.1371/journal.pone.0274863
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of cytomegalovirus infection among women in Saudi Arabia: A cross-sectional study

Abstract: Background Cytomegalovirus (CMV) is the most common intrauterine congenital infection in humans. Worldwide seropositive rates of CMV are considerably high among women of childbearing age. There is currently no optimal drug treatment nor a vaccine for congenital CMV infection and therefore the best available program to date of prevention is practicing standard hygienic measures. The success of this program relies on women’s knowledge of CMV modes of transmissions, and risk and preventative behaviors. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Indeed, a study conducted in Japan between 2012 and 2016 showed no change in knowledge about the virus in the population of pregnant women, who maintained an extremely low knowledge rate over the study years (7% over 6 years) [46]. A low level of CMV-related knowledge was also found among woman of childbearing age and/or pregnant woman in other studies [45,[47][48][49][50]. This rate varies greatly from one country to another, with a percentage of knowledge of less than 20% reported in some studies conducted in Ireland, the USA, Holland, Japan, Saudi Arabia, and Australia [32,[47][48][49][51][52][53].…”
Section: Evolution Of Awareness In Pregnant Womenmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, a study conducted in Japan between 2012 and 2016 showed no change in knowledge about the virus in the population of pregnant women, who maintained an extremely low knowledge rate over the study years (7% over 6 years) [46]. A low level of CMV-related knowledge was also found among woman of childbearing age and/or pregnant woman in other studies [45,[47][48][49][50]. This rate varies greatly from one country to another, with a percentage of knowledge of less than 20% reported in some studies conducted in Ireland, the USA, Holland, Japan, Saudi Arabia, and Australia [32,[47][48][49][51][52][53].…”
Section: Evolution Of Awareness In Pregnant Womenmentioning
confidence: 91%
“…A comparison between women's knowledge of CMV and knowledge of other infections or diseases that can infect the fetus has been conducted by some authors. All results showed that women's knowledge of CMV was much lower than their knowledge of toxoplasmosis or Down syndrome, which, however, have a lower incidence than CMV infection [44,48,50,53,56,57,59,60]. In the United States, the number of children born with cCMV and its long-term sequelae is estimated at 8600 per year, which is much higher than the number of children born over the same period with sequelae due to toxoplasmosis and Down syndrome (about 1000 and 4000 cases, respectively), which are diseases that are better known by women [59].…”
Section: Awareness Compared To Other Conditionsmentioning
confidence: 95%
“…Previous studies suggested slightly higher CMV seroprevalence in women, possibly due to lower awareness and preventive measures, especially among women of lower socioeconomic status. Additionally, the increase in all‐cause mortality linked to CMV may be influenced by the specific age distribution, with women being slightly older in our study 18–20 . The analysis by ethnicity showed that CMV was associated with higher mortality risks in all ethnic groups, but confidence intervals were wider in non‐Hispanic black and Mexican Americans due to smaller sample sizes.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, the increase in all-cause mortality linked to CMV may be influenced by the specific age distribution, with women being slightly older in our study. [18][19][20] The analysis by ethnicity…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of CMV Infection Among Pregnant Women with Cord Blood Examination Africa with the following rates 30-90%, 58.3%, 94.4%, 80-90%, 92-100%, 60-100% respectively. 23 In Iraq several studies had been implemented to find out the prevalence of CMV among women which range from 77.3% in Babylon to 95.7% in Kirkuk, while in Erbil the prevalence was 100%. [24][25][26] The higher prevalence rate in the current study is in consistent with high prevalence rate in Iraq which is over 95%.…”
Section: Originalmentioning
confidence: 99%